Effects of Rosmarinus officinalis L. aerial parts essential oil on intact memory and scopolamine-induced learning deficits in rats performing the Morris water maze task - H Hosseinzadeh (Journal of Medicinal Plants, 2004)
In this study, the effect of Rosmarinus officinalis aerial parts essential oil was studied on intact memory and scopolamine-induced learning deficits in rats performing the Morris water maze task. The oil was injected intraperitoneally to rats 0.5 h before training for 5 consecutive days. During the training period, four trials were carried out each day. on the 5th day of the experiment, the locomotor activity was assesed using open field test. The oil at the doses of 125-250 mg/kg decreased the latency time to find the platform. The effect of the oil was also evaluated on hyoscine (0.5 mg/kg)-induced learning deficits in rats. The oil reduced the effect of hyoscine on memory. In the open field activity test, the oil at the doses 125-250 mg/kg did not change locomotor activity. The higher dose of rosemary (500 mg/kg) reduced the factors of open field test. The co-administration of oil with hyocine significantly compensated the reduction of locomotor activity in hyosine group alone. On the basis of these results, the R. officinalis aerial parts essential oil improved intact memory and the hyoscine impaired acquisition/performance activity. These agents can potentially be introduced as new drugs in the treatment of cognitive dysfunctions such as Alzheimerchr('39')s disease.